Approaches to the Structuring of Educational Material Technical Disciplines - Gernichenko, Ivan (Pedagogical Discourse, 2015)
In the article the problem of systematization and structuring of educational information has been considered by the author. It has been noted that the forming of knowledge, skills, abilities and personal qualities of students is possible due to information and the information presented to students can reflect the same object of study with various degrees of thoroughness and detalization. Based on this there is a need for structural analysis and selection of criteria for assessing the completeness of the information content. It has been noted that the selection of the content is based on the general didactic principles and specific statements offered in the theories of stage forming of mental actions, program, modular and task-activity training. Models of logical structure of the educational material and main approaches to the structuring of technical subjects content (discrete, systematic-functional, systematic-structural, systematic-logical) have been analyzed. It has been pointed out that the basis for structuring the content of educational material for technical subjects should include the systematic-structural approach to the activities of didactic system based on the achievement of the ultimate goal of education, that is contributing to the thorough assimilation of those sections and training programs topics that are the most significant. The structure of such a system is stable, as the connections among the individual elements are quite exactly defined by the logic of science and psychological-pedagogical requirements to subjects and learning technologies in general. It has been concluded that the essence of the structuring process is to identify the system of semantic connections among elements of content (knowledge) of large didactic units (academic subject, section, topic) and to arrange educational material in the sequence, which is caused by the system of connections.